(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Twelve species of genera Diplotremina Kristan-Tollmann, 1960, Duostomina Kristan-Tollmann, 1960, and Variostoma Kristan-Tollmann, 1960 have been described from the Norian and Rhaetian strata of the Slovenian Basin (eastern Southern Alps). A lamellar wall structure has been confirmed for Duostomina and observed for the first time in Variostoma. The multi-layered nature of the lamellae of Diplotremina and Duostomina may be a result of a diagenetic alteration of the single-layered lamellae. The position of Variostoma in the family Duostominidae remains doubtful due to the alveolar nature of its wall.